Multigenerational Consequences of Prenatal Exposure to Benzophenone-3 Demonstrate Sex- and Region-Dependent Neurotoxic and Pro-Apoptotic Effects in Mouse Brain - Karolina Przepiórska-Drońska; Andrzej Łach; Bernadeta Angelika Pietrzak-Wawrzyńska; Joanna Rzemieniec; Małgorzata Kajta; Agnieszka Wawrzczak-Bargieła; Wiktor Bilecki; Karolina Noworyta; Agnieszka Wnuk (Toxics)
Benzophenone-3 (BP-3), commonly used as a UV filter in personal care products and as a stabilizer, is an alleged endocrine disruptor with potential neurodevelopmental impacts. Despite its abundance in the environment, the studies on its effect on brain development are scarce, especially in terms of multigenerational impact. In this work, for the first time, we examined neurotoxic and pro-apoptotic effects of BP-3 on mouse brain regions (cerebral cortex and hippocampus) in both the first (F1) and second (F2) generations after maternal exposure to environmentally relevant BP-3 levels. We found disregulated markers of cell damage (LDH, H2O2, caspase-3 and -8) and observed increased expression of pro-apoptotic Fas/FAS or Fasl/FASL. BP-3 exposure disrupted the BAX/BCL2 pathway, showing stronger effects in the F1 than in the F2 generation, with a dominance of extrinsic pathway (FAS, FASL, caspase-8) over intrinsic one (BAX, BCL2), suggesting that BP-3-induced apoptosis primarily operates via the extrinsic pathway and could impair brain homeostasis across generations. This study underscores the potential of BP-3 to increase multigenerational risks associated with disrupted neurodevelopment and highlights the importance of understanding its long-term neurotoxic effects.